2015
DOI: 10.1124/jpet.115.227389
|View full text |Cite
|
Sign up to set email alerts
|

Altered ProteinS-Glutathionylation Identifies a Potential Mechanism of Resistance to Acetaminophen-Induced Hepatotoxicity

Abstract: Acetaminophen (APAP) is the most commonly used over-thecounter analgesic. However, hepatotoxicity induced by APAP is a major clinical issue, and the factors that define sensitivity to APAP remain unclear. We have previously demonstrated that mice nulled for glutathione S-transferase Pi (GSTP) are resistant to APAP-induced hepatotoxicity. This study aims to exploit this difference to delineate pathways of importance in APAP toxicity. We used mice nulled for GSTP and heme oxygenase-1 oxidative stress reporter mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 57 publications
1
22
1
Order By: Relevance
“…While McGarry and colleagues suggested that protein glutathionylation confers a protective effect to Gstp1/2 -/-mice against APAP toxicity (75), it is difficult to compare with our findings for the following reasons. Our findings are drawn from a straightforward comparison between APAP-exposed and control HepaRG cells (rather than against a more complicated background of GSTP knockout).…”
Section: Apap-induced Protein Glutathionylation Is Dose and Bioactivacontrasting
confidence: 40%
“…While McGarry and colleagues suggested that protein glutathionylation confers a protective effect to Gstp1/2 -/-mice against APAP toxicity (75), it is difficult to compare with our findings for the following reasons. Our findings are drawn from a straightforward comparison between APAP-exposed and control HepaRG cells (rather than against a more complicated background of GSTP knockout).…”
Section: Apap-induced Protein Glutathionylation Is Dose and Bioactivacontrasting
confidence: 40%
“…The overexpression of GST in mammalian tumor cells has been implicated in the resistance to various anti-cancer agents and chemical carcinogens [17]. Additionally, in acetaminophen-induced hepatotoxicity recent work has shown that downregulation of GST-Pi could prevent toxicity by increasing S-glutathionylation of GCL, protecting its integrity and increasing GSH synthesis [18,19]. For a detailed view of GSH-regulated antioxidant mechanisms and other enzymatic systems related to GSH the readers are referred to Espinosa-Diez et al [20].…”
Section: Glutathione Synthesismentioning
confidence: 99%
“…The authors concluded that whereas GSTP may be an important determinant of protein S-glutathionylation in response to oxidative/nitrosative stress, its role as a fundamental component of the Sglutathionylation process is limited. Compared with wild-type mice, only a subset of proteins with significantly altered peptide ratios were identified in GSTP-null mice [111].…”
Section: Gstp In Cell Signaling: Jnk Activation and Protein S-glutathmentioning
confidence: 96%
“…Significant enrichment of S-glutathionylated mitochondrial and Krebs cycle proteins suggests an involvement of this modification in energy metabolism processes in vivo. However, little overall difference between the hepatic protein S-glutathionylation profiles between wild-type and GSTP-null mice was demonstrated [111]. The authors concluded that whereas GSTP may be an important determinant of protein S-glutathionylation in response to oxidative/nitrosative stress, its role as a fundamental component of the Sglutathionylation process is limited.…”
Section: Gstp In Cell Signaling: Jnk Activation and Protein S-glutathmentioning
confidence: 99%